2012
DOI: 10.7589/0090-3558-48.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Infection of Marine Mammals in the Pacific Northwest, 1997–2010

Abstract: ABSTRACT:Q fever is a zoonotic disease caused by the bacterium Coxiella burnetii. Humans are commonly exposed via inhalation of aerosolized bacteria derived from the waste products of domesticated sheep and goats, and particularly from products generated during parturition. However, many other species can be infected with C. burnetii, and the host range and full zoonotic potential of C. burnetii is unknown. Two cases of C. burnetii infection in marine mammal placenta have been reported, but it is not known if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 9 publications
(14 reference statements)
1
34
0
Order By: Relevance
“…C. burnetii infection in a marine mammal was first confirmed in the placental tissue of a rescued Pacific harbor seal in California [Lapointe et al 1999]. Subsequent investigations have found evidence of C. burnetii infection in the Steller sea lion , as well as in the Pacific harbor seal, harbor porpoise, and Northern fur seal [Lapointe et al 1999;Duncan et al 2012;Kersh et al 2012]. A recent study did find C. burnetii seropositivity was detected in 34% of 215 Pacific harbor seals sampled in the Pacific Northwest .…”
Section: Appendix A: Background Information On Zoonotic Infections Q mentioning
confidence: 92%
“…C. burnetii infection in a marine mammal was first confirmed in the placental tissue of a rescued Pacific harbor seal in California [Lapointe et al 1999]. Subsequent investigations have found evidence of C. burnetii infection in the Steller sea lion , as well as in the Pacific harbor seal, harbor porpoise, and Northern fur seal [Lapointe et al 1999;Duncan et al 2012;Kersh et al 2012]. A recent study did find C. burnetii seropositivity was detected in 34% of 215 Pacific harbor seals sampled in the Pacific Northwest .…”
Section: Appendix A: Background Information On Zoonotic Infections Q mentioning
confidence: 92%
“…Natural infections have been reported in domestic birds and in wild birds Astobiza et al 2011). In terrestrial as well as in marine wildlife the presence of C. burnetii has been confirmed in roe deer, wild boars, rodents, European hare, pacific harbour seal, a Steller sea lion, Northern fur seals and harbour porpoises (Thompson et al 2012;Astobiza et al 2011;Lapointe et al 1999;Kersh et al 2012;Kersh et al 2010;Duncan et al 2012). These data indicate a sylvatic cycle for C. burnetii, in which ticks probably play an important role as vector.…”
Section: Host Rangementioning
confidence: 99%
“…The indirect immunofluorescensce assay (IFA) using antigens derived from both Nine Mile phase 1 and phase 2 strains was conducted at either the Centers for Disease Control and Prevention in Atlanta, Georgia or Colorado State University in Fort Collins, Colorado. The protocol was conducted as previously des cribed (Kersh et al 2012) using FITC-labeled goat anti-ferret (KPL) as a secondary antibody to detect binding. To prevent reporting of cross-reactive antibodies and false positives, the positive result cutoff was set at 1:128.…”
Section: Methodsmentioning
confidence: 99%
“…Placental disease (Kersh et al 2010) and high placental and seroprevalence have been reported in Pacific harbor seals Phoca vitulina, harbor porpoises Phocoena phocoena and Steller sea lions Eumetopias jubatus (SSL) of the Pacific Northwest (Kersh et al 2012). In Alaska, approximately 75% of northern fur seal Callorhinus ursinus (NFS) placentas tested positive for C. burnetii by real-time PCR (qPCR) (Duncan et al 2012(Duncan et al , 2013 and there is a high seroprevalence in both the NFS and the sympatric SSL populations (Minor et al 2013).…”
Section: Introductionmentioning
confidence: 99%